Rare weather phenomena and the work of large-format roof coverings - Ksit, Barbara; Szymczak-Graczyk, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Wind action belongs to loads that are environmentally variable. Wind action is included in the basic combination of loads, whereas hurricane wind action is classified as a unique combination. Due to large gusts of wind, the roof coverings of large-scale buildings are exposed to detachment of their cover layer.
Keywords: wind load; hurricane wind; roof covering; damage; membrane; sail effect; obciążenie wiatrem; huragan; pokrycie dachu; uszkodzenie; membrana; efekt żagla